Causal effective field theories - Gonzalez,MC; de,Rham C; Pozsgay,V; Tolley,AJ (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2022)
Physical principles such as unitarity, causality, and locality can constrain the space of consistent effective field theories (EFTs) by imposing two-sided bounds on the allowed values of Wilson coefficients. In this paper, we consider the bounds that arise from the requirement of low energy causality alone, without appealing to any assumptions about UV physics. We focus on shift-symmetric theories, and consider bounds that arise from the propagation around both a homogeneous and a spherically symmetric scalar field background. We find that low energy causality, namely the requirement that there are no resolvable time advances within the regime of validity of the EFT, produces two-sided bounds in agreement with compact positivity constraints previously obtained from 2→2 scattering amplitude dispersion relations using full crossing symmetry.